2019
DOI: 10.1186/s12903-019-0781-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical studies investigating immediate and short-term efficacy of an occluding toothpaste in providing dentine hypersensitivity relief

Abstract: Background Dentine hypersensitivity (DH) can occur after gum recession or enamel loss and may impact quality of life. Treatments include toothpastes that decrease DH by occluding dentine tubules. One effective occluding ingredient used in toothpastes is stannous fluoride (SnF 2 ), but this can be unstable in aqueous formulation. These three studies aimed to characterise the short-term effects of an experimental, anhydrous SnF 2 dentifrice on DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Therefore, increased frequency of treatment caused more surface precipitation and greater tubule occlusion, leading to a greater reduction in HD and a greater benefit for dentin hypersensitivity relief. Randomized clinical studies of Creeth et al 25 also indicated that dentin hypersensitivity reduced after single brushing with 0.454% SnF 2 toothpaste and significantly greater reduced after 3 days twice-daily use. However, after 7 days, SnF 2 with-iontophoresis group showed deeper dentinal tubule occlusion than SnF 2 without-iontophoresis group.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, increased frequency of treatment caused more surface precipitation and greater tubule occlusion, leading to a greater reduction in HD and a greater benefit for dentin hypersensitivity relief. Randomized clinical studies of Creeth et al 25 also indicated that dentin hypersensitivity reduced after single brushing with 0.454% SnF 2 toothpaste and significantly greater reduced after 3 days twice-daily use. However, after 7 days, SnF 2 with-iontophoresis group showed deeper dentinal tubule occlusion than SnF 2 without-iontophoresis group.…”
Section: Discussionmentioning
confidence: 94%
“…They did not notice any differences in microbiome diversity. Creeth et al [ 41 ] investigated in a short-term clinical study, how a stannous fluoride toothpaste could reduce DH compared to brushing with a conventional toothpaste after single use. This toothpaste, effectively, reduced DH on evaporative and tactile stimuli after a three-day treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al [ 35 ], comparing stannous fluoride group with potassium nitrate and placebo, affirmed that the use of potassium nitrate could alleviate tooth sensitivity during and after in-office bleaching. Creeth et al [ 41 ] demonstrated how brushing with an experimental anhydrous 0.454% SnF 2 polyphosphate toothpaste reduced DH with a single use and better in three days use.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Based on this theory, the main strategy to treat DH is to reduce dentin permeability by blocking/occluding dentinal tubules. [9][10][11] Current materials for dentinal tubule occlusion include sodium fluoride/stannous fluoride, [12][13][14] strontium chloride/acetate, 15,16 potassium oxalate, [17][18][19] arginine, 20,21 calcium phosphate and its composites, [22][23][24][25][26][27][28][29][30][31] bioglass and silicates, [32][33][34][35][36][37][38][39][40][41][42][43] laser, 44,45 gallic acid (tannin)/Fe 3+ complex, 47,48 amyloid-like aggregation coating, 49 and selfassembly peptide. 51 Although some of these demonstrate clinical effectiveness in tooth desensitization, no treatment regimen presently exhibits long-lasting efficiency in treating DH.…”
Section: Introductionmentioning
confidence: 99%